2022
DOI: 10.1016/j.ijid.2022.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ADAMTS13 Activity in Correlation with Pathophysiology, Severity, and Outcome of COVID-19: A Retrospective Observational Study

Abstract: Background Low ADAMTS 13 Activity has been suggested as an interplaying factor in the pathogenesis of COVID-19, considering that it is a thrombo-inflammatory disease with high risk of microthrombosis. Objectives The study aimed to explore the correlation between ADAMTS13 activity and the pathophysiological pathway of COVID-19. Patients/Methods We carried out a retrospective observational study of 87 COVID-19 patients in Nmc Royal Hospital, Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Further investigation revealed negative antibodies to ADAMTS13, and the panel for congenital TTP was negative. The remaining hypothesis was that TTP was related to SARS-CoV-2 infection 10 or to a laboratory error. Anemia recurred in 2 weeks, and further investigation revealed a cobalamin deficit, which in a 5-month-old infant that is exclusively breastfed, narrows the differential diagnosis to a maternal deficiency and a primary inherited defect of metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed negative antibodies to ADAMTS13, and the panel for congenital TTP was negative. The remaining hypothesis was that TTP was related to SARS-CoV-2 infection 10 or to a laboratory error. Anemia recurred in 2 weeks, and further investigation revealed a cobalamin deficit, which in a 5-month-old infant that is exclusively breastfed, narrows the differential diagnosis to a maternal deficiency and a primary inherited defect of metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[37] The time to viral clearance was significantly prolonged in obese patients with low ADAMTS13 activity; the same result was reported by our research team in a previous study. [21] Delayed viral clearance and poor outcomes in obese patients are hallmark findings of several studies. [39,40] Reduced ADAMTS13 activity was one of the most obvious drivers of unmet treatment outcomes in this special patient population, highlighting the importance of rigorous assessment of hospitalized obese COVID-19 patients, regardless of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In a previous study by our group, we found that reduced ADAMTS13 activity was associated with the development of pneumonia, the need for mechanical ventilation, and the severity of COVID-19; however, there was no statistically significant association with mortality. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies neutralize or accelerate the clearance of ADAMTS13, thereby inhibiting the breakdown of vWF. 18,19 This results in the accumulation of oversized vWF multimers in arterioles and capillaries. In light of the recent pandemic, a novel link has been discovered between COVID-19 and TMA conditions, including TTP.…”
Section: Discussionmentioning
confidence: 99%